Epithelial-specific keratin gene expression: identification of a 300 base-pair controlling segment. - Jiang, C K (1990)
To elucidate the elements required for regulation of keratin expression in epidermis, we have linked a short, 300 base pair segment, corresponding to the promoter region of a human K#14 gene, to the chloramphenicol-acetyl-transferase gene. This construct was introduced into various mammalian cell lines and primary cultures via Ca3(PO4)2 precipitation. The 300 base pair segment from the keratin gene promoter region was active in all epithelial cells studied including transformed, simple epithelial cells such as HeLa and ME-180, cell lines derived from stratified epithelium, such as SCC-12, as well as primary cultures of epithelial cells. The construct was inactive in all non-epithelial cells tested including fibroblasts and melanocytes. The segment does not function as a silencer in nonepithelial cells but it can function as an enhancer in epithelial cells. Using the polymerase chain reaction we have constructed a series of deletions of the promoter and have localized an essential function within a 40 bp sequence. We conclude that we have identified the keratin gene promoter that is sufficient to confer epithelial-specific expression.